The aspherical explosions of the 03fg-like Type Ia supernovae 2021zny and 2022ilv revealed by polarimetry - Nagao, T.; Maeda, K.; Mattila, S.; Kuncarayakti, H.; Gutierrez, C. P.; Cikota, A. (EDP Sciences, 2025)
Context. A peculiar subtype of Type Ia supernovae (SNe), 03fg-like (super-Chandrasekhar) SNe, show different observational properties from prototypical Type Ia SNe: they typically have high luminosities at the light-curve peak, low expansion velocities, and strong carbon features. The origin of this class of Type Ia SNe has been actively debated. Recent nebular-phase infrared observations of the 03fg-like Type Ia SN 2022pul using the James Webb Space Telescope revealed large-scale asymmetries in the ejecta and the presence of the strong [Ne II] line at 12.81 mu m, suggesting a violent merger of two white dwarfs as its origin.
Aims. Polarimetry is another powerful tool for studying the overall ejecta asymmetries of spatially unresolved SNe. Here, we aim to check the universality of the violent merger scenario as the origin of 03fg-like Type Ia SNe, by studying their explosion geometries using polarimetry.
Methods. In this Letter we present imaging-polarimetric observations of the two 03fg-like Type Ia SNe 2021zny and 2022ilv.
Results. SNe 2021zny and 2022ilv show high intrinsic polarization (similar to 1%-similar to 2%), which might be composed of multiple components with different polarization angles. This indicates that they have complex aspherical structures in their ejecta, supporting the violent merger scenario for their origin. Our observations provide the first clear evidence from polarimetry for such aspherical structures.